Taking care of what we have: participatory natural resource management on the Caribean Coast of Nicaragua / Patrick Christie, David Blandford, Ray Garth, Bonifacio González, Mark Hostetler, Oswaldo Morales, Roberto Rigby, Bertha Simmons, Eduardo Tinkam, Grabriel Vega, Ronnie Benooy, Noreen White - Christie, Patrick (Nicaragua : CIDCA, 2000)
CAMPlab the coastal area monitoring project and laboratory, the process matures and expands, focusing on the management plan; walking a fine line,the dynamics of the participatory action researche process, historical context, taking care of the nature resources base, insecurity and tensions, demanding accountrability; workaing with the peoplñe, lessons learned, achieving PAR goals, moving toward critical consciousness, enabling and constraining factors, changing the institutional approach.
Incluye índice, imágenes, tablas, mapas, grafica de barra y bibliografía
Col. RN
Keywords: 1. CONSERVACIÓN-RECURSOS NATURALES-COSTA ATLÁNTICA (NICARAGUA) 2. ECOLOGÍA COSTERA-COSTA ATLÁNTICA 3. PROTECCIÓN-MEDIO AMBIENTE 4. RECURSOS NATURALES 5. AGROFORESTAL